2016
DOI: 10.15761/nfo.1000123
|View full text |Cite
|
Sign up to set email alerts
|

The optic nerve and peripapillary vasculature in albinism

Abstract: Albinism, an inherited disorder resulting in reduced ocular melanin, is usually associated with reduced best-corrected visual acuity, nystagmus, foveal hypoplasia, and iris transillumination. However, a spectrum of findings has been reported, with foveal hypoplasia, nystagmus, and misrouting of the retinostriate fibers having been purported to cause reduced visual acuity. The purpose of this case-controlled study is to describe the optic nerve anatomy and peripapillary retinal vasculature in albinism and to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Conley et al (2016) described abnormal features of the optic disc and peripapillary vasculature, including mild optic nerve hypoplasia and central vessels emerging and extending nasally from the optic disc in albinism compared with controls. 20 This was supported by findings of Neveu et al (2005), who reported that retinal vasculature in albinism tends to be more asymmetric with a reduced number of arterial vessel branches. 21 However, these studies lacked quantitative methods for analyzing vessel architecture, and did not correlate vessel morphology with clinical features such as foveal morphology.…”
supporting
confidence: 61%
“…Conley et al (2016) described abnormal features of the optic disc and peripapillary vasculature, including mild optic nerve hypoplasia and central vessels emerging and extending nasally from the optic disc in albinism compared with controls. 20 This was supported by findings of Neveu et al (2005), who reported that retinal vasculature in albinism tends to be more asymmetric with a reduced number of arterial vessel branches. 21 However, these studies lacked quantitative methods for analyzing vessel architecture, and did not correlate vessel morphology with clinical features such as foveal morphology.…”
supporting
confidence: 61%
“…However, no relationship was found between the VA and the described optic nerve abnormalities. 31 In our series, the RNFL analysis was limited to the mean RNFL thickness. The RNFL thickness in the OCA population has very rarely been described in the literature.…”
Section: Discussionmentioning
confidence: 99%